1997
DOI: 10.1292/jvms.59.953
|View full text |Cite
|
Sign up to set email alerts
|

Sporicidal Activities of Disinfectants on Paenibacillus larvae.

Abstract: ABSTRACT. Sporicidal activities of glutaraldehyde, sodium hypochlorite, povidone iodine, ethylene oxide gas, chlorhexidine gluconate, and didecyl dimethylammonium chloride on wet and dry spores of Paenibacillus larvae (basonym: Bacillus larvae) were evaluated for control of honeybee American foulbrood. Glutaraldehyde was found to have a strong and rapid effect on both the wet and the dry spores among the disinfectants tested. -KEY WORDS: disinfectant, Paenibacillus larvae, sporicidal activity.J. Vet. Med. Sci.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…To corroborate our findings, we did an EST with bleach. We found that spores were effectively destroyed by concentrations corresponding with those found by Okayama et al . (1997).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…To corroborate our findings, we did an EST with bleach. We found that spores were effectively destroyed by concentrations corresponding with those found by Okayama et al . (1997).…”
Section: Resultssupporting
confidence: 84%
“…These results seem to be somewhat con¯icting with those published by Okayama et al (1997). These authors found that low concentrations (0á05%) of sodium hypochlorite were suf®cient to destroy P. larvae subsp.…”
Section: Chemical Disinfectioncontrasting
confidence: 40%
See 1 more Smart Citation
“…However, information concerning the use of iodophores in the area of beekeeping is scarce. Only a slow‐acting sporicidal effect of highly concentrated povidone‐iodine on Paenibacillus larvae spores has been described …”
Section: Introductionmentioning
confidence: 99%
“…Only a slow-acting sporicidal effect of highly concentrated povidone-iodine on Paenibacillus larvae spores has been described. 13 Seven of the eight most common viruses infecting Apis mellifera (reviewed by Manley et al 14 ) are members of order Picornavirales. 15,16 15 Physicochemical properties of both f. Iflaviridae and f. Dicistroviridae have not been fully established.…”
Section: Introductionmentioning
confidence: 99%